P134 Maintaining confidentiality in sexual health clinics; a local and national service evaluation. (30th June 2016) - Duffield, Rebecca; Clarke, Emily; Poree, Mickaela; Lamb, Tony; Tang, Alan; Foley, Elizabeth; Patel, Raj
Abstract : Background/introduction: The need for confidentiality is of particular importance in sexual health clinics, as patients are sometimes reluctant to give personal contact information due to fears of disclosure to other parties. This can cause difficulties for clinicians when trying to issues results or advise patients of the need to attend for follow up. Aim(s)/objectives: To review the proportion of patients with Chlamydia Trachomatis who had their confidentiality/permissions (CP) breached in order to issue results, or who never received their results. To review UK wide policy in sexual health clinics on these issues. Methods: The EPRs of those attending a large provincial Sexual Health Department with a new diagnosis of Chlamydia Trachomatis between July 2014 and June 2015 were reviewed. A nationwide policy survey regarding breaches in CP in order to provide patients with results was disseminated to Lead Clinicians. Results: The records of 605 patients were reviewed. 4% had their CP breached, of whom 18 (69%) required follow up only, and 31% for the issue of positive results post treatment. 5% did not receive their results. 62 (25%) of sexual health clinics returned surveys, of whom 16 (26%) had a policy for issuing results when breaches were required. Discussion/conclusion: Breaching CP in order to issue results or ask patients to attend for follow up, or failing to give results, was common, affecting nearly 1 in 10 patients. The survey showed that a minority of UK clinics have formal policies addressing this issue. A BASHH national guideline would be helpful.